An overview of malaria elimination efforts in South Kalimantan from 2010 to 2018 - Muhammad Rasyid Ridha; Deni Fakhrizal; Syarif Hidayat; Evi Liani (International Journal of Public Health Science (IJPHS), 2021)
Malaria elimination in Kalimantan is targeted to be completed by 2020. This study aimed to analyze efforts to eliminate malaria in South Kalimantan from 2010-2018. This research is a descriptive study of the population of South Kalimantan who is at risk of suffering from malaria. This study used a total participation technique involving all cases of malaria recorded in the malaria surveillance information system (SISMAL) 2010-2018 for South Kalimantan. The data used are secondary data obtained from the South Kalimantan Provincial Health Office in 2010-2018, namely the number of suspected malaria cases, confirmation and inspection, treatment use data, bed nets distribution, village stratification and annual parasite incidence (API) in each district. The results showed that there was the trend of malaria elimination efforts in South Kalimantan was increased from 89% of suspected patients in 2010 to 100% in 2018, and trend of API decreased from 1.5‰ in 2010 to 0.21‰ in 2018. So, with the provision of artemisinin combination therapy (ACT), from 78% in 2010 increased to 100% in 2018. All regencies/cities in South Kalimantan showed API number <1‰ in 2018. Stratification of high case incidence (HCI) villages/sub-district in 2018 decreased compared to 2010, from 211 villages to 19 villages, while malaria-free stratification from 0 in 2010 to 1,761 villages. Malaria elimination efforts in South Kalimantan showed a significant increase and it is expected that 2020 South Kalimantan will be free of malaria.